Disruption of Crosstalk between Mesenchymal Stromal and Tumor Cells in Bone Marrow as a Therapeutic Target to Prevent Metastatic Bone Disease. Issue 12 (December 2014) - Gordon, Jonathan A. R.; Lisle, Jennifer W.; Alman, Benjamin A.; Lian, Jane B.
<x xml:space="preserve">Abstract</x> Skeletal metastasis is a serious complication of many primary cancers. A common feature of tumor cells that metastasize to the bone marrow microenvironment is that they initiate a cascade of events, recruiting and presumably/potentially altering the phenotype of bone marrow mesenchymal stromal cells (MSC) to produce an environment that allows for tumor growth and in some cases, drug‐resistant dormancy of latent cancer cells. Consequently the MSC population can contribute to metastatic disease through several distinct mechanisms by differentiating into cancer‐associated fibroblasts (CAFs). Understanding the expression and epigenetic changes that occur as normal MSCs become associated with metastatic tumors would reveal possible therapeutic targets for treating skeletal metastasis. J. Cell. Physiol. 229: 1884–1886, 2014. © 2014 Wiley Periodicals, Inc.